MAXIMIZATION OF DNA DAMAGE TO MGMT(+) EGFR(+) GBM CELLS USING OPTIMAL COMBINATION OF TEMOZOLOMIDE-ANTI EGFR MONOCLONAL ANTIBODY NIMOTUZUMAB - Inggas, Made Agus Mahendra; Wahjoepramono, Eka J.; Maliawan, Sri; Islam, Andi Asadul (BALI MEDICAL JOURNAL, 2015)
Background: Glioblastoma multiforme (GBM) is the most aggressive primary brain tumor in adultswith dismal prognosis due to the unavailability of an effective therapy. Up to now, there had been no definitive studies published on EGFR inhibition therapy as a chemosensitizer for GBM therapy using Temozolomide (TMZ). This study aims to reveal the most effective method and timing to administer TMZ anti EGFR targeted therapy which causes maximal DNA damage on GBM cells. Methods: Various regimens of anti EGFR monoclonal antibody Nimotuzumab (NMZ) was administered in different combinations with TMZ, performed on U87MG MGMT(+) EGFR(+) cells. The effectiveness of the combinations were evaluated by measuring yH2AX levels which reflects the degree of DNA damage. One-way Anova and LSD tests were performed to determine the effects of each treatment with p